226k views
3 votes
Solve the following equation for x. x = -2 x = 2 x = -17 x = -7 (x - 5)/2 = -6

User Laryn
by
5.5k points

1 Answer

6 votes

Explanation:

x= -2,

(x - 5) / 2= -6

( (-2) - 5) / 2= -6

(-7) / 2 = -6

-3.5 = - 6

right hand side not equal to left hand side of this equation.so,x= -2 cannot exist for this equation.

x=2,

(x - 5) / 2= -6

(2 - 5) / 2= -6

(-3) / 2= -6

-1.5 = - 6

right hand side not equal to left hand side of this equation.so,x= 2 cannot exist for this equation.

x= -17

(x - 5) / 2= -6

( ( -17) - 5) / 2= -6

(- 22) / 2= -6

-11 = -6

right hand side not equal to left hand side of this equation.so,x= -17 cannot exist for this equation.

x= -7,

(x - 5) / 2= -6

( ( -7) -5) / 2= -6

(-12) / 2= -6

-6= -6

right hand side equal to left hand side of this equation.so,x= -7 exist for this equation.

User Abhinandan Pratap
by
5.4k points